Performance of different vegetable oil-diesel blends used in a single cylinder diesel engine - Banania, Amarlo A. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The continued depletion of fossil fuels, due to the ever-increasing demand for energy in the face of a growing global population, presses the need to come up with alternative fuel solutions. The non-renewability of fossil fuels cause harmful emissions on the environment has prompted many countries to provide funding for the research and development of viable alternative energy sources. Findings have shown that vegetable oils can be produced on a larger scale to be used in biodiesel and doing so may generate livelihood and help stimulate the economy. This study aims to contribute technical information on the performance of vegetable oil-neat diesel fuel blends (using jatropha, corn and palm oils) in a diesel engine. Testing was done using a single cylinder, vertical type, four-stroke cycle, naturally aspirated diesel engine genset with 6.3 kW rated power, and a direct injection system. Engines of this capacity would be used to generate emergency power for small to medium size households and shops, for camping, irrigation pumps, and other agricultural machinery. Different blends of vegetable oils with neat diesel were used at varying engine speeds and loads. Specific fuel consumption, efficiency and maximum power output were measured and compared. This study showed that the blends up to 20% by volume of refined corn oil (RCO) refined palm oil (RPO), jathropa filtered oil (JFO) and jathropa methyl ester (JME) with neat diesel fuel can be used in a small single-cylinder diesel engine genset. Fuel consumption (SFC) of the various vegetable oil blends differed by -11% to +15% relative to diesel fuel. RPO and JFO blends tended to have lower SFC than neat diesel by up to 11%. SFC of RCO and JME blends were close to or higher than that of neat diesel up to 15%. Fuel conversion efficiency of the various vegetable oil blends differed by -12% to +15% relative to diesel fuel. RCO and JME blends tended to have lower efficiency than neat diesel by 12%. Efficiencies of RPO and JFO blends were close to or higher than that of neat diesel up to 15%. Power output of the various vegetable oil blends differ by -8% to +6% relative to diesel fuel. RPO and JME blends tended to have lower power output than neat diesel up to 8%. Power output of RCO and JFO blends were close to or higher than that of diesel up to 6%. The higher thermal efficiency of the vegetable oil-diesel blends may be due to their lower heating value than and comparable power output to neat diesel for the same load, 15% of RPO-diesel blend was best SFC of all test fuels while 10% of JFO-diesel blend was best power output of all test fuels. It is the hope that with information generated from this study, the use of biofuels would gain more ground in the country.
Thesis (M.S. Mechanical Engineering)--University of the Philippines, Diliman
Keywords: Diesel motor -- Alternative fuels; Vegetable oils as fuel